2006
DOI: 10.1097/01.prs.0000221111.89812.ad
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Morbidity and Mortality on Admission to a Burn Unit

Abstract: Using objective measurements in burn treatment is of great importance. The formulas presented by the authors explain a considerable percentage of the probability of morbidity in burn victims. The authors suggest that other burn units develop their own statistically supported prediction models.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
31
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 18 publications
6
31
0
3
Order By: Relevance
“…[11,12] Smoke inhalation injury is generally considered to be the strongest predictor of burn mortality. [13] In our burn population, however, we found that the presence of preexisting medical comorbidities had significant impact on mortality as evident by significant reduction in LA50 in those aged ≤ 65 years. In addition, we found the measured effect of comorbidities to be most pronounced in patients ≤ 18, suggesting that younger patients with medical comorbidities are more susceptible to worse outcomes.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…[11,12] Smoke inhalation injury is generally considered to be the strongest predictor of burn mortality. [13] In our burn population, however, we found that the presence of preexisting medical comorbidities had significant impact on mortality as evident by significant reduction in LA50 in those aged ≤ 65 years. In addition, we found the measured effect of comorbidities to be most pronounced in patients ≤ 18, suggesting that younger patients with medical comorbidities are more susceptible to worse outcomes.…”
Section: Discussionmentioning
confidence: 48%
“…Previous studies examining mortality from burns have identified three major risk factors associated with increased mortality: age > 60 years old, TBSA > 40%, and presence of inhalation injury. [11][12][13] Presence of all three risk factors is associated with mortality of 90%. [11,12] Smoke inhalation injury is generally considered to be the strongest predictor of burn mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Al contrario, en nuestro estudio sólo fueron incluidos pacientes adultos GQ, quienes presentan una mayor gravedad y mortalidad (29% de mortalidad global), lo que permite un mejor estudio de factores predictores. Meshulam-Derazon y cols 16 analizaron los predictores de mortalidad y morbilidad en 249 pacientes admitidos a la unidad de quemados de centro médico de Rabin (Telaviv) entre 1995 y 2002. La SCQ y la injuria inhalatoria fueron los únicos factores predictores independientes de mortalidad, y el tipo de quemadura no se asoció a mortalidad ni a morbilidad.…”
Section: Discussionunclassified
“…En nuestro estudio, la quemadura eléctrica por alto voltaje no se asoció a una mayor estadía hospitalaria, hallazgo que concuerda con lo publicado por otros autores 7,16 . Al ser un centro de referencia nacional, muchos de los pacientes que ingresan a nuestra unidad han iniciado su tratamiento en otro centro, donde a su vez regresan cuando se ha logrado la estabilización clínica y la cobertura cutánea completa.…”
Section: Discussionunclassified
“…(24) Although one group of authors also observed an increase in mortality, the presence of SII provided little additional data for predicting mortality when the percentage of TBSA burned and age were used as prognostic factors. (25) Another group of authors used a formula to retrospectively predict fatal outcomes in 530 patients, concluding that patients who presented more than 40% TBSA burned, were older than 60 years of age and had SII were at a higher risk of death, mortality being as high as 95% when all three of these factors are present.…”
Section: Discussionmentioning
confidence: 99%